Clinical efficacy of Endostar continuous infusion combined with concurrent chemoradiotherapy in the treatment of oesophageal squamous cell carcinoma - Du, Xinglong; Ji, Yuting; Qin, Wenqiang; Wei, Jie (Frontiers in Medicine, 2024)
Objective: To evaluate the effectiveness and safety of concurrent chemoradiotherapy using Endostar continuous infusion for treating oesophageal squamous cell carcinoma (OSCC). Method: A total of 62 patients with oesophageal carcinoma were divided into three groups: the Endostar continuous infusion group (n = 27), the Endostar intravenous drip group (n = 21) and the concurrent chemoradiotherapy group (n = 14). All patients underwent oesophageal radiotherapy (56–60 Gy) alongside concurrent chemotherapy (4 mg of raltitrexed + 100 mg of oxaliplatin, two cycles). In the Endostar continuous infusion group, 210 mg of Endostar was administered via infusion once every 3 weeks for 72 hours, repeated for two cycles. The Endostar intravenous drip group received a dosage of 15 mg/day of Endostar, administered once daily for 14 days, repeated for two cycles. The objective response rate (ORR) (complete remission + partial remission), progression-free survival (PFS), 2-year overall survival (2y-OS) and adverse reactions were observed. Results: In the Endostar continuous infusion, intravenous drip and concurrent chemoradiotherapy groups, the ORR was 100%, 95.2% and 78.6%, respectively (P < 0.05). There was a statistically significant difference between the continuous infusion and concurrent chemoradiotherapy groups (P < 0.05). However, there was no statistically significant difference between the continuous infusion and intravenous drip groups or the intravenous drip and concurrent chemoradiotherapy groups (P > 0.05). The continuous infusion and intravenous drip groups had higher PFS rates than the concurrent chemoradiotherapy group (P < 0.05). Regarding the 2y-OS rate, no statistically significant difference was observed among the three groups (P > 0.05). Furthermore, there was no statistically significant difference in adverse reactions among the groups (P > 0.05). Conclusion: Concurrent chemotherapy based on endostatin is effective and safe in the treatment of OSCC. Continuous 3-day Endostar infusion treatment can significantly enhance both short- and long-term therapy efficacy in patients while maintaining a high level of safety.